On the identities of Senecio lanatus and Senecio populifolius. Issue 4 (27th December 2018) - Anderberg, Arne A.; Jarvis, Charlie
Abstract: Original material of Senecio lanatus L. and Senecio populifolius L., two names that are not in current use, has been located. It is concluded that, in both cases, this material is identifiable as the South African species currently known as Senecio verbascifolius Burm. f., a name that postdates the two Linnaean names. Lectotypes for the three names are selected and it is concluded that nomenclatural stability would be best served by proposing the rejection of the two Linnaean names.